Effect of water washing on reactivities and NOx emission of Zhundong coals. Issue 4 (November 2016) - Wang, Chang'an; Liu, Yinhe; Jin, Xi; Che, Defu
Abstract: Zhundong coalfield is one super-huge coalfield newly discovered in China. However, ash-related problems have occurred due to its high content of alkali metals. Water washing is a possible approach to improve its utilization while little research was conducted on Zhundong coals. This study deals with the effect of water washing on alkali metal removal, thermal behaviors, and NO x emission of Zhundong coals. Experimental results show that water-soluble sodium is the predominant chemical form accounting for 70–92% of total sodium, while the case of potassium is different. The pore structure shows a considerable change after being washed. Sodium can be effectively removed while the removal ratio is closely related to water temperature and washing time. The mean apparent activation energy of coal pyrolysis decreases after being washed at low temperature, while high temperature of washing water hinders the pyrolysis. Certain sodium has a catalytic effect on pyrolysis while excessive sodium exhibits inhibitory influence. The conversions of fuel-N to NO and to N2 O of washed coals are higher than those of raw coals. Water washing has a slight negative effect on NO x emission and combustion reactivity which is related to the catalytic effect of sodium within coal structure. Highlights: Zhundong coals are characterized by high content of water-soluble sodium. Sodium can be effectively removed with pore features obviously changed. The coal pyrolysis is brought forward after being washed at low temperature. Water washing presents negative effect on NO x emission and combustion reactivity.